A Different Way to Stay in Touch with ‘Urban Nature’: The Perceived Restorative Qualities of Botanical Gardens - Carrus, Giuseppe; Scopelliti, Massimiliano; Panno, Angelo; Lafortezza, Raffaele; Colangelo, Giuseppe; Pirchio, Sabine; Ferrini, Francesco; Salbitano, Fabio; Agrimi, Mariagrazia; Portoghesi, Luigi; Semenzato, Paolo; Sanesi, Giovanni (Frontiers in Psychology, 2017)
Botanical gardens represent interesting arenas for research in environmental psychology and environment-behavior relations. They can be considered a very particular type of restorative environment and also have a relevant social function for the promotion of a more sustainable lifestyle in current societies. In this paper, we present a study assessing the relationship between the perceived restorativeness, the psychological and physical benefits experienced, and the subjective well-being reported by visitors of botanical gardens in four different cities in Italy (N = 127). As expected, a bootstrapping mediation model supported the idea that perceived restorativeness of botanical gardens significantly predicts visitors’ subjective well-being, both directly and indirectly through perceived physical and psychological benefits of the visit. A moderation model also revealed that the relationship between restorativeness and well-being varies across respondents with different socio-demographic characteristics, being stronger for singles as compared to couples with and without children, respectively. The theoretical and practical implications of these findings are discussed.